Alpha-lipoic acid suppresses Nε-(carboxymethyl) lysine-induced epithelial mesenchymal transition in HK-2 human renal proximal tubule cells. (2nd December 2018) - Lo, Mei-Chen; Chen, Ming-Hong; Hsueh, Yu-Ting; Kuo, Yung-Ting; Lee, Horng-Mo
Abstract: N ε -(carboxymethyl) lysine (CML) plays causal roles in diabetic complications. In the present study, we investigated whether CML-induced HIF-1α accumulation and epithelial-mesenchymal transition (EMT) in HK-2 renal proximal tubular epithelial cells. Treatment with CML-BSA increased reactive oxygen species (ROS) production reduced the mitochondrial membrane potential and induced mitochondrial fragmentation. Pre-treatment of cells with antioxidant, α-lipoic acid, normalised the ROS production and restored the mitochondrial membrane potential. These changes were accompanied with morphological changes of epithelial mesenchymal transition. CML-BSA increased the protein level of hypoxia-inducible factor-1α (HIF-1α), and the EMT-associated transcription factor, TWIST. These effects were reversed by α-lipoic acid. CML-BSA increased the protein levels of mesenchymal-specific markers, including vimentin, α-smooth muscle actin, which were alleviated by pre-treatment with α-lipoic acid. Our data suggest that CML-BSA induces EMT through a ROS/HIF-1α/TWIST-dependent mechanism, and that α-lipoic acid may alleviate the CML-induced EMT in renal tubular cells.